ANALISIS KARAKTER DISIPLIN SEBAGAI WUJUD KESADARAN HUKUM PEDAGANG KAKI LIMA TERHADAP PERATURAN DAERAH NOMOR 12 TAHUN 2016 PASCA PENERTIBAN DI PASAR TALANG BANJAR JAMBI - Dea Natasya Yohanna; Priazki Hajri; Khusnul Khotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and analyze the factors influencing the formation of disciplined character among street vendors in complying with Regional Regulation Number 12 of 2016 after the enforcement actions at Talang Banjar Market, Jambi City, as well as to analyze the government’s efforts in fostering disciplined character as a manifestation of legal awareness among street vendors. This study employed a qualitative approach with a descriptive type of research. Data were collected through interviews, observations, and documentation from local government documents, enforcement archives, official reports, activity photographs, and previous studies related to street vendors. The informants in this study were divided into three categories: primary informants (street vendors), key informants (the Legal Division of the Regional Secretariat of Jambi City or members of the Jambi City Regional House of Representatives involved in drafting Regional Regulation Number 12 of 2016), and additional informants (community members around Talang Banjar Market, Jambi City). The collected data were analyzed using qualitative data analysis techniques, including data reduction, data presentation, and conclusion drawing, while data validity was tested through source, technique, and time triangulation.The results of the study indicate that the disciplined character of street vendors at Talang Banjar Market, Jambi City, after the enforcement actions is still low due to economic factors, long-standing trading habits, and the low internalization of legal values. Meanwhile, government efforts through socialization, relocation, business facilities, and enforcement actions have not been fully effective because they still focus on physical control measures and have not optimally built legal awareness and a sustainable culture of discipline among street vendors.